(untitled) (International Journal of Engineering and Computer Science, 2015)
A housing society and its functions are a part of our everyday lives. Members of the managing committee are those who take charge of all the chores involved here. Residents often feel edgy regarding undone jobs and most even lack time to keep track of all these happenings. But, there’s no avoiding the fact that these chores and all the housing society members are inseparable. This paper presents the design and implementation of an Android based society maintenance application. The elements of this system comprise of (1) an Android application which will be accessed by both managing committee and residents (2) database server that will contain information entered by the users as well as generated for the users and (3) business logic that will interconnect and pass information between the application and the database server. Our application is developed in Eclipse.